Youth advocacy varies in relation to adult advisor characteristics and practices in gender-sexuality alliances. Issue 3 (3rd July 2022) - Poteat, V. Paul; O'Brien, Michael D.; Yang, Megan K.; Rosenbach, Sarah B.; Lipkin, Arthur
Abstract: With growing attention to youth's efforts to address sexual and gender diversity issues in gender-sexuality alliances (GSAs), there remains limited research on adult advisors. Do advisor characteristics predict their youth members' advocacy? Among 58 advisors of 38 GSAs, we considered whether advisor attributes predicted greater advocacy by youth in these GSAs ( n  = 366) over the school year. GSAs varied in youth advocacy over the year. Youth in GSAs whose advisors reported longer years of service, devoted more time to GSA efforts each week, and employed more structure to meetings (to a point, with a curvilinear effect), reported greater relative increases in advocacy over the year (adjusting for initial advocacy and total meetings that year). Relative changes in advocacy were not associated with whether advisors received a stipend, training, or whether GSAs had co-advisors. Continued research should consider how advisors of GSAs and other social justice-oriented groups foster youth advocacy.